Korzyści i zagrożenia w zakresie zmian strukturalnych polskiej gospodarki związane z członkostwem w Unii Europejskiej - Ładysz, Jerzy (Benefits and Threats for Structural Changes in Polish Economy Connected with Membership in the European Union, 2008)
In the article have been discussed chosen benefits and threats for structural changes in Polish economy connected with membership in the European Union. European structural policy should be only additional one to the market-driving structural changes in the Polish economy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 136-146